Constraints to livelihood diversification of rural farmers in selected areas of Patuakhali district (Bangladesh Journal of Agricultural Research, 2019)
The present study was aimed at determining the constraints confronted by the farmers in livelihood diversification. The purposes of this study were to determine the extent and nature of livelihood diversification of the farmers and also to explore relationships of 13 selected characteristics of the farmers with their livelihood diversification. There were a total of 1270 farmers in the 5 villages constituted the population of the study, out of which 10 percent of the total farmers were selected through simple random sampling technique. This gave a sample size of 127 such farmers. Data were collected by the researcher himself with the help of pre-tested interview schedule during 15 February 2013 to 30 March, 2013. The livelihood diversification scores of the respondents ranged from 0.22 to 0.79 with an average of 0.41. It is seen that more than half of the farmers 53.5% had medium level of livelihood diversification compared to 19.7 percent of them having low livelihood diversification and 26.8 percent had high livelihood. Out of 13 selected characteristics of the farmers, seven of those viz. education, family education, income generating experience, household annual income, communication exposure, organizational participation and attitude towards livelihood diversification had positive significant relationship with livelihood diversification.Bangladesh J. Agril. Res. 44(2): 355-365, June 2019